Quantitative determination of al (III) traces in soft drink, pharmaceutical products and biological fluids of kidney failure and alzheimer disease patients using carbon sensor - Basset, M. H. Abdel; Zayed, M. A.; Frag, Eman Yossri (Scientific Reports, 2026)
Carbon paste sensor based on p-chlorophenyl maleanilic acid (pCl-MA) as an ionophore was synthesized and investigated as an Al(III) ion selective sensor. The developed sensor shows Nernstian slope of 20.32 ± 1.18 mV decade− 1 over the working concentration range of 1.0 × 10− 6 − 1.0 × 10− 1 mol L− 1 of Al (III) ion with a detection limit of 3.3 × 10− 7 mol L− 1. The sensor exhibited a stable potential response in the pH range from 4.0 to 6.0 and a fast response time of 8 s. The prepared sensor indicated a very good selectivity to Al (III) over a variety of cations. The sensor could be easily employed for determination of Al (III) ions in pharmaceutical products, soft drink and biological fluids of kidney failure and Alzheimer disease patients. The reaction mechanism between pCL-MA and Al (III) was confirmed by FT-IR spectroscopic analysis, SEM and EDX.